Tissue engineering applications in otolaryngology—The state of translation. Issue 4 (19th June 2020) - Niermeyer, Weston L.; Rodman, Cole; Li, Michael M.; Chiang, Tendy
Abstract: While tissue engineering holds significant potential to address current limitations in reconstructive surgery of the head and neck, few constructs have made their way into routine clinical use. In this review, we aim to appraise the state of head and neck tissue engineering over the past five years, with a specific focus on otologic, nasal, craniofacial bone, and laryngotracheal applications. A comprehensive scoping search of the PubMed database was performed and over 2000 article hits were returned with 290 articles included in the final review. These publications have addressed the hallmark characteristics of tissue engineering (cellular source, scaffold, and growth signaling) for head and neck anatomical sites. While there have been promising reports of effective tissue engineered interventions in small groups of human patients, the majority of research remains constrained to in vitro and in vivo studies aimed at furthering the understanding of the biological processes involved in tissue engineering. Further, differences in functional and cosmetic properties of the ear, nose, airway, and craniofacial bone affect the emphasis of investigation at each site. While otolaryngologists currently play a role in tissue engineering translational research, continued multidisciplinary efforts will likely be required to push the state of translation towards tissue‐engineered constructs available for routine clinical use. Level of Evidence: NA. Abstract : This review appraises the state of head and neck tissue engineering over the past five years, with a specific focus on otologic, nasal, craniofacial bone, and laryngotracheal applications. While there have been promising reports of effective tissue‐engineered interventions in small groups of human patients, the majority of research remains constrained to in vitro and in vivo studies aimed at furthering the understanding of the biological processes involved in tissue engineering. Differences in functional and cosmetic properties of the ear, nose, airway, and craniofacial bone affect the emphasis of investigation at each site.